The Pain Outcomes Comparing Yoga vs. Structured Exercise (POYSE) Trial in Veterans With Fibromyalgia: Study Design and Methods - Allsop, Vivianne L.; Schmid, Arlene A.; Miller, Kristine K.; Slaven, James E.; Daggy, Joanne K.; Froman, Amanda; Kline, Matthew; Sargent, Christy; French, Dustin D.; Ang, Dennis; Van Puymbroeck, Marieke; Schalk, Nancy L.; et al. (Frontiers in Pain Research, 2022)
Background Fibromyalgia is a common pain condition that often leads to significant disability. Unfortunately, the effectiveness of most medications for fibromyalgia is limited, and there is a need for alternative, non-pharmacological therapies. Yoga and aerobic exercise are both evidence-based non-pharmacological treatments for fibromyalgia. However, no prior studies have directly compared the effectiveness of yoga vs. exercise. Objective This article describes the study design and recruitment outcomes of the Pain Outcomes comparing Yoga vs. Structured Exercise (POYSE) Trial, a two-arm randomized comparative effectiveness trial. Methods Veterans with fibromyalgia, defined by the 2010 American College of Rheumatology diagnostic criteria, who also experienced at least moderate pain severity were enrolled. The participants were randomized to a 12-week yoga-based or a structured exercise program (SEP) and will undergo comprehensive outcome assessments at baseline, 1, 3, 6, and 9 months by interviewers blinded to treatment assignment. The primary outcome will be the overall severity of fibromyalgia as measured by the total Fibromyalgia Impact Questionnaire-Revised. Secondary outcomes included depression, anxiety, health-related quality of life, pain beliefs, fatigue, sleep, and self-efficacy. Results A total of 2,671 recruitment letters were sent to potential participants with fibromyalgia. Of the potential participants, 623 (23.3%) were able to be contacted by telephone and had their eligibility assessed. Three hundred seventy-one of those interviewed were found to be eligible (59.6%) and 256 (69.0%) agreed to participate and were randomized to the YOGA (n = 129) or the SEP (n = 127) arm of the trial. Conclusions Clinicians are faced with numerous challenges in treating patients with fibromyalgia. The interventions being tested in the POYSE trial have the potential to provide primary care and other care settings with new treatment options for clinicians while simultaneously providing a much needed relief for patients suffering from fibromyalgia. Trial Registration Funded by VA Rehabilitation Research and Development (D1100-R); Trial registration: ClinicalTrials.gov, NCT01797263.